University students and excessive screen time: links to sleep disturbance and acute health issues - Abdullah Kamil, Najiyya; Ahmad, Norfaezah; Ahmad, Norhidayah (IIUM Press, 2025)
Background: University students often spend a significant amount of time on screens due to academic demands, entertainment and social interactions. However, excessive screen time may negatively affect sleep quality and contribute to deterioration in health. This study aimed to determine the association between sleep disturbance and acute health effects associated with prolonged screen time among students at a higher education institution.